Impact of Bank Size on Its Financial Indicators in Bulgaria - Vаtev, Zhelyo; Marinov, Marin; Ismailov, Taner (Dr. Viktor Koval, 2022)
Introduction. One of the frequently used criteria for classifying banks is according to their size. The question of the existence of a dependence between the size of credit institutions, on the one hand, and their financial condition and results of activity, on the other hand, was logically raised. In recent years, this issue has increased its significance in Bulgaria against the background of the following circumstances: first, a process of consolidation of the banking sector in the country has begun; second, the new dimensions of the macroprudential policy impose higher regulatory requirements on banks, according to Basel III regulations; third, there is a significant number of relatively small credit institutions whose activity has a relatively limited scope; fourth, weak economic activity and low rate of economic growth of the country; fifth, the search for ways to increase the efficiency of banking activity. Aim and tasks. The aim of the research is to establish the extent to which the size of the credit institutions in the country has an impact on various aspects of banking activity, as well as the strength of this impact. The subject of the study is focused on delineating the comparative advantages and disadvantages of big and small banks in terms of the scale of their operations. Results. The analysis is based on information on the status and results of the activities of 18 banks in Bulgaria. The study covers observations on the development of the banking sector in 2020 and 2021. When specifying the size of banks, the traditional criterion is used, which is most often used to determine their size, namely the amount of their assets. It examines the impact of the size of credit institutions on 7 financial indicators reflecting different aspects of banking activity: Return on Assets, Efficiency of Administrative Costs, Staff Productivity, Asset Quality, Asset risk rating, Liquidity Coverage Ratio, Total Capital Ratio. On this basis, a correlation analysis is made, in which the correlation coefficient is used as the statistical measure of the dependence between the size of credit institutions (the assets), on the one hand, and their financial indicators, on the other hand. In parallel, the average values of the analyzed indicators for the respective years are calculated separately for each group of banks. Conclusions. There is reason to claim that one of the possible instruments for increasing the efficiency of the banking sector in the country is its further consolidation. Of course, the conclusions drawn are not universal. This reflects the specifics of the banking industry in Bulgaria and the specifics of the period to which the analyzed data refer. With almost all analyzed indicators, a strong or moderate dependence between the size of the banks and the values of the considered financial indicators is outlined. This dependence is most pronounced in relation to the Return on Assets– as the size of credit institutions increases, the return on their assets increases significantly. The values with credit institutions with a wider scale of activity are better, which gives them visible advantages over other smaller banks.